The complete critical guide to Thomas Hardy - Harvey, Geoffrey, 1943- (Complete critical guide to English literature., 2003)
This guide provides students with a lucid introduction to Hardy's life and works and the basis for a sound comprehension of his work. It includes the major aspects of Hardy's life in the context of contemporary culture a detailed commentary on Hardy's most important work and a critical map of Hardy's complete writing an outline of the vast body of criticism that has built up around Hardy's work with examples of recent critical debate. Both exposition and guide, this volume enables students to form their own readings of one of the most important writers of the nineteenth century.